Capsule endoscopy: New Technology That is Here to Stay - Robert Enns (Canadian Journal of Gastroenterology)
Capsule endoscopy (CE) has recently been approved as a new technique for the examination of the small intestine. Following approval by the Food and Drug Administration of the United States in August 2001, CE has quickly gained widespread acceptance as the new 'gold standard' for visualization of the small intestine. Food and Drug Administration approval was based on two clinical studies (1,2). The first (1) compared CE with push enteroscopy (PE) (the previous gold standard) in dogs who had nine to 13 beads (3 mm to 6 mm each) sewn into the small intestine. CE identified more beads (median of six) than PE (median of three), with 64% sensitivity compared with 37% sensitivity for PE. The authors concluded that this new method of assessing the small intestine was superior to PE.